Diagnosis and treatment of Helicobacter pylori infections in children and elderly populations - Chao Peng (KeAi Communications Co., Ltd., 2019)
Helicobacter pylori (H. pylori) infection is associated with various gastric and extra-gastric diseases. Importantly, this infection is the strongest known risk factor for gastric cancer (GC). H. pylori eradication can effectively prevent H. pylori infection-associated diseases in H. pylori-positive patients, including children and elderly subjects. However, a limited selection of antibiotics, a higher reinfection rate, and certain spontaneous clearance rates, to some extent, restrict the choice of H. pylori treatments in pediatrics. In addition, it is imperative to perform an accurate diagnosis of H. pylori infection in children by determining the presence of the H. pylori infection and the underlying cause of symptoms. In elderly patients, poor tolerance to drugs and higher sensitivity to adverse effects are major concerns during H. pylori therapy. Recent studies have demonstrated that H. pylori eradication could significantly lower the GC risk in the elderly population. The benefit and risk of H. pylori eradication in elderly patients should be comprehensively considered and balanced. If available, susceptibility-based tailored therapies may be preferable in eradicating H. pylori. In addition, to increase the eradication rate and reduce adverse effects, new therapeutic strategies (e.g., probiotic supplementation, berberine supplementation, dual therapy) for H. pylori infection are being extensively investigated. The impact of H. pylori eradication with antibiotics on the microbiota in children has been explored, but further high-quality studies are crucial to delineate the extent of H. pylori eradication affecting the microbial community in children. In this review, we summarize the current understanding of H. pylori diagnosis and treatment in children and the elderly population and aim to provide insights into the efficient management and treatment implementation in these populations. Keywords: Children, Elderly, Helicobacter pylori, Diagnosis, Treatment